Sex-specific association of low-renin hypertension with metabolic and musculoskeletal health in Korean older adults - Seunghyun Lee; Jae Seung Chang; Jae Seung Chang; Kyu-Sang Park; Sang-Baek Koh; Moon Young Kim; Moon Young Kim; Moon Young Kim; Jung Soo Lim (Frontiers Media S.A., 2024)
IntroductionLow-renin hypertension (LRH) accounts for approximately one-third of patients with hypertension and are more prevalent in women and the older adult population. Previous study has found a link between the renin-angiotensin-aldosterone system (RAAS) and sex hormones. However, there are insufficient data on the relationship between LRH and metabolic or musculoskeletal outcomes in older adults.Methods and materialsAmong the 343 participants from a population-based cohort study conducted between May 2018 and August 2019, a total of 256 (86 men older than 50 years and 170 postmenopausal women) were included. The presence of LRH was defined as plasma renin activity (PRA) <1 ng/mL/h and systolic blood pressure (BP) ≥130 or diastolic BP ≥80 mmHg based on the 2017 ACC/AHA guidelines. Individuals with missing data, and those who had used medications that could affect PRA within the past six months were excluded. Bone mineral density (BMD), trabecular bone score (TBS), and appendicular lean mass (ALM) index were assessed using dual-energy X-ray absorptiometry; degraded TBS was defined as partially degraded to degraded levels (≤1.350). Muscle function was assessed according to the Asian Working Group for Sarcopenia guidelines. PRA was measured using radioimmunoassay.ResultsThe median age was 66 [61-72] years, and the body mass index (BMI) was 24.7 [23.0-26.4] kg/m2. Individuals with LRH, accounting for 34.8%, had lower diabetes mellitus; more dyslipidemia; and poorer muscle function, BMD, and TBS than those in the non-LRH group. In addition, PRA was positively correlated with C-peptide, HOMA-IR, TBS, and ALM index. After adjusting for covariates including age and BMI, LRH was negatively associated with femur neck T-score (adjusted β = −0.30, 95% CI [−0.55 to −0.05], p = 0.021) and the presence of LRH was significantly associated with degraded TBS in women (adjusted odds ratio = 3.00, 95% CI [1.36-6.58], p = 0.006).ConclusionOur findings suggest that LRH can influence clinical features and metabolic risk in older adults. Notably, LRH in postmenopausal women was linked to lower femur neck T-scores and degraded TBS, indicating sex-specific effects of LRH on bone health. Larger prospective studies are required to elucidate how changes in the RAAS affect metabolic and musculoskeletal outcomes in older adults.